Décollement des fondations sous séisme : méthodes temporelles et temps/fréquence - Clouteau, Didier; Devesa, Georges (European Journal of Computational Mechanics, 2002)
A comparison of time-domain and time-frequency domains algorithms is proposed to study the uplift of building foundations during earthquakes. The time-frequency approach is based on a detailled model of the soil using a BEM in the frequency domain and using the Green’s functions of a layered elastic half-space. In this case, uplift is accounted for using an iterative quasi-Newton scheme operating on the entire time range. At each iteration step, the quasi-tangent operator is built by mean of a stochastic linearisation based on statistics of the current solution and is inverted in the frequency domain. The TD approach is based on classical penalty techniques in the FEM representing the soil by an equivalent layer of springs that are calibrated using the results of the BE model. These two approaches are compared on a real case consisting of a reactor-building resting on a layered soil.